Transformation of Mecardonia (Plantaginaceae) with wild-type Agrobacterium rhizogenes efficiently improves compact growth, branching and flower related ornamental traits - Perez De La Torre, Mariana (2018)
Mecardonia constitutes an emergent crop in the floriculture market. In order to develop plants with improved compact growth by molecular breeding, we transformed Mecardonia cv. ‘Guarani Amarilla INTA’ using a wild-type strain of Agrobacterium rhizogenes. An advantage of using this approach is that generated plants are stable and considered non-GMO in several countries. Adventitious roots were produced by inoculating Mecardonia shoots with agropine ATCC15834 strain. Twenty independent root cultures regenerated spontaneously into shoots in hormone-free medium and presence of TL-DNA oncogenes were confirmed in their genomes. We selected four root inducing (Ri)-lines, designated GME, GCA, GVI and GIN, based on their different degree of compact growth habit. Under greenhouse conditions representative Ri-lines displayed reduced internode and shoot length, shoot and root biomass, aerial plant coverage, individual leaf area, flower width, pedicel length and the number of flowers per plant; and increased the number of nodes, axillary shoots, flower density and flower width relative to aerial plant coverage and mostly normal flowering when compared to non-transformed plants. To correlate phenotypical traits with gene expression, quantitative PCR analysis was performed. Ri-line GIN showed the highest rolA-D and ORF8, ORF13-14 gene expression which correlated with its super-dwarf phenotype, whereas the most weak Ri-phenotype observed in Ri-line GME showed no presence of rolA and ORF8 genes in plant genome. Expression of rolD and ORF13 correlated with reduced aerial plant coverage, shoot weight, shoot: root ratio and increased flower density and flower width relative to plant coverage, thus being considered of particular interest in Mecardonia breeding. Expression of ORF8 and rolA correlated with reduced aerial plant coverage, pedicel length, the total number of flowers per plant and increased flower width relative to the aerial plant coverage. Moreover, ORF8 and ORF13 may have a more prominent role in plant development than previously assumed and assigned to rol-genes. Overall, a better-organized compact growth without affecting other traits could be generated.